Oliver Hülden, Das griechische Befestigungswesen der archaïschen Zeit. Entwicklungen – Formen – Funktionen - Lohmann, Hans (Journal of Greek Archaeology, 2021)
This extensive and lavishly illustrated work is based on the Munich habilitation thesis of the author and is the most comprehensive treatment of the subject to date. The regrettably long-neglected Greek fortifications have received increased attention in recent years and decades. The extensive bibliography (pp. 523-560) lists over 700 titles, two of which are particularly noteworthy because they deal with the same subject: F. Lang, Archaische Siedlungen in Griechenland. Struktur und Entwicklung (Berlin 1996) and R. Frederiksen, Greek City Walls of the Archaic period (Oxford 2011). The latter goes back to a dissertation from 2001 and for that reason alone justifies a renewed in-depth study of the Archaic fortifications of the Greek world.